A novel therapeutic approach to plane warts - Miljković, Jovan (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2012)
Warts are benign epithelial poliferations of the skin and mucosa caused by infection with human papilloma viruses (HPV). Plane warts are mainly caused by HPV-3 and HPV-10. There is no single treatment that is absolutely effective, and different types of treatment may be combined. One must take into account the possibillity of spontaneous regression, and so the therapeutic approach should not be too aggressive. Two case reports are presented of two immunocompetent patients with multiple plane warts successfully treated with low-dose systemic isotretinoin.
Keywords: Bradavice; dermatologija; Isotretinoin; Izotretionin; Therapy; Warts; Zdravljenje